Neuroanatomical basis for cholinergic modulation of locomotor networks by sacral relay neurons with ascending lumbar projections. Issue 15 (5th May 2014) - Finkel, Eran; Etlin, Alex; Cherniak, Meir; Mor, Yoav; Lev‐Tov, Aharon; Anglister, Lili
ABSTRACT Synaptic excitation by sacrocaudal afferent (SCA) input of sacral relay neurons projecting rostrally through the ventral white matter funiculi (VF neurons) is a potent activator of the hindlimb central pattern generators (CPGs) in rodent spinal cords lacking descending supraspinal control. Using electrophysiological recordings from the sacral and lumbar spinal segments, we show that the motor output of the lumbar segments produced by SCA stimulation is enhanced by exposing the sacral segments of the neonatal rat spinal cord to the acetylcholinesterase inhibitor edrophonium (EDR). Histochemical and immunostaining of the sacral cord reveals expression of acetylcholinesterase activity, ability to synthesize acetylcholine, and/or innervation by cholinergic synaptic inputs in significant proportions of fluorescently back‐labeled sacral VF neurons. Moreover, the majority of the VF neurons express M2 muscarinic receptors, raising the possibility that the elevated acetylcholine levels resulting from inhibition of acetylcholinesterase act on such receptors. Indeed, sacral application of atropine or the M2‐type receptor antagonist methoctramine was found to reverse the effects of EDR. We suggest that variations in the sacral level of acetylcholine modulate the SCA‐induced locomotor rhythm via muscarinic receptor‐dependent mechanisms and that the modified activity of sacral VF neurons in the presence of an acetylcholinesterase inhibitor can be partially ascribed to the cholinergic components associated with them. Thus, pharmacological manipulations of the sacral cholinergic system may be used to modulate the locomotor‐related motor output in the absence of descending supraspinal control. J. Comp. Neurol. 522:3437–3455, 2014. © 2014 Wiley Periodicals, Inc.